The effect of socioeconomic status on age at diagnosis and overall survival in patients with intracranial meningioma. (3rd April 2022) - Brewster, Ryan; Deb, Sayantan; Pendharkar, Arjun Vivek; Ratliff, John; Li, Gordon; Desai, Atman
Abstract: Background: Intracranial meningiomas are the most common primary tumors of the central nervous system. How socioeconomic status (SES) impacts treatment access and outcomes for brain tumor subtypes is an emerging area of research. Few studies have examined the relationship between SES and meningioma survival and management with reference to relevant clinical factors, including age at diagnosis. We studied the independent effects of SES on receiving surgery and survival probability in patients with intracranial meningioma Methods: 54, 282 patients diagnosed with intracranial meningioma between 2003 and 2012 from the Surveillance, Epidemiology, and End Results (SEER) Program at the National Cancer Institute database were included. Patient SES was divided into tertiles. Patient age groups included 'older' (>65, the median patient age) and 'younger'. Multivariable linear regression and Cox proportional hazards model were used with SAS v9.4. Results were adjusted for race, sex, and tumor grade. Kaplan–Meier survival curves were constructed according to SES tertiles and age groups. Results: Meningioma prevalence increased with higher SES tertile. Higher SES tertile was also associated with younger age at diagnosis (OR = 0.890, p < 0.05), an increased likelihood of undergoing gross total resection (GTR) (OR = 1.112, p < 0.05), and a trend toward greater 5-year survival probability (HR = 1.773, p = 0.0531). Survival probability correlated with younger age at diagnosis (HR = 2.597, p < 0.001), but not with GTR receipt. Conclusion: The findings from this national longitudinal study on patients with meningioma suggest that SES affects age at diagnosis and treatment access for intracranial meningiomas patients. Further studies are required to understand and address the mechanisms underlying these disparities.